Leishmania promastigotes: building a safe niche within macrophages - Moradin, Neda; Descoteaux, Albert (Frontiers in Cellular and Infection Microbiology, 2012)
Upon their internalization by macrophages, Leishmania promastigotes inhibit phagolysosome biogenesis. The main factor responsible for this inhibition is the promastigote surface glycolipid lipophosphoglycan (LPG). This glycolipid has a profound impact on the phagosome, causing periphagosomal accumulation of F-actin and disruption of phagosomal lipid microdomains. Functionally, this LPG-mediated inhibition of phagosome maturation is characterized by an impaired assembly of the NADPH oxidase and the exclusion of the vesicular proton-ATPase from phagosomes. In this chapter, we review the current knowledge concerning the nature of the intra-macrophage compartment in which Leishmania donovani promastigotes establish infection. We also describe how LPG enables this parasite to remodel the parasitophorous vacuole.